INFLUENCE OF PHYSICAL AND SOCIAL FACTORS ON PLACE ATTACHMENT IN DE MANDAILING CAFE - Kusumowidagdo, Astrid; Michelle, Aubrey (Ide dan Dialog Desain Indonesia (Idealog), 2023)
In this modern era, after the end of the pandemic, cafes are back as the third space of choice for the majority of urban communities. Of ices and homes are no longer a priority as a place to do of ice tasks or school and campus assignments. The purpose of this study is to see visitors' perceptions of the interior of DeMandailing cafe in West Surabaya whether physical and social factors affect the increase in productivity while working in the cafe. The research method was carried out by means of a case study to 100 people with an age limit of 18-40 years, where they filled out a survey to determine place attachment based on physical factors and social factors. Physical factors include cleanliness aroma, natural lighting, artificial lighting, furniture comfort, music and acoustics, the decor used, and social factors include the desire to stay long, feeling a sense of belonging, the ability to feel territorial, having feelings of trust for staf , increased productivity, the desire and opportunity to socialize with others. The conclusion obtained in terms of physical factors, the design in the cafe succeeds in attracting visitors to enter and is comfortable to work and socialize with others. In terms of social factors, it is also quite supportive, but still needs to improve the design so that it becomes a stimuli to encourage socialization activities. Keywords : Place attachment, cafe interior, physical factors, social factors.